2019
DOI: 10.1111/ajag.12707
|View full text |Cite
|
Sign up to set email alerts
|

Accommodation payment plans in residential aged care: The impact of consumer choice

Abstract: Objective To examine changes in accommodation payments to residential aged care facilities following the introduction of consumer choice reforms in 2014. These reforms have allowed residents to choose between making lump sum refundable deposits and/or rental‐style payments. Methods Quantitative analysis was undertaken for facility‐level quarterly data of 136 separate facilities, which were operated by six providers over the period under study. Results While the total pool of payments has grown strongly, consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…These variations are demonstrated in a recent study of 136 RACH which found that from 2014 to 2019, the share of their capital pool coming from RADs fell from 96% to just under 80%, with a commensurate rise in DAP income. The impacts on balance sheets of highly leveraged providers, especially in the private sector, and the likely need to adjust business models were noted 37 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These variations are demonstrated in a recent study of 136 RACH which found that from 2014 to 2019, the share of their capital pool coming from RADs fell from 96% to just under 80%, with a commensurate rise in DAP income. The impacts on balance sheets of highly leveraged providers, especially in the private sector, and the likely need to adjust business models were noted 37 …”
Section: Discussionmentioning
confidence: 99%
“…The impacts on balance sheets of highly leveraged providers, especially in the private sector, and the likely need to adjust business models were noted. 37 The consumer perspective presents a less certain picture. From the outset, the Productivity Commission recognised that although growing wealth indicated increasing capacity of coming cohorts to pay for accommodation, those at the older end of the retirement spectrum were likely to have lower assets and more would be eligible for some subsidy than indicated in its projections based on the total population aged 65 and over.…”
Section: Howementioning
confidence: 99%